Aortoarteritis: A rare pulmonary-renal disease - Karande, Tanvee Prasad; Nayak , Aditya M (Indian Journal of Case Reports, 2024)
Takayasu arteritis (TAK) is an autoimmune disease majorly affecting young females. It alters the vascular wall, resulting in stenosis, occlusion, or dilatation. It has no distinct clinical manifestation. Here, we present the case of an 18-year-old girl who presented with generalized tonic-clonic seizure and hypoxia. Blood investigations showed deranged urea and creatinine values. Computed tomography angiography revealed bilateral artery occlusion, decreased kidney size, and pulmonary artery dilatation, confirming generalized vascular disease that caused hypertension and ischemic nephropathy in the patient. Our case represents a rare autoimmune disease, leading to pulmonary hypertension and renal artery stenosis. TAK should be considered as a differential diagnosis in young female patients presenting with pulmonary as well as renal signs and symptoms, especially if there is discrepancy in blood pressure levels in all limbs.Case summary- An 18yr old girl presented with generalized tonic-clonic seizure and hypoxia. Blood investigations showed deranged urea and creatinine values. CT angiography revealed occlusion of bilateral arteries along with decreased size of both the kidneys. It also revealed pulmonary artery dilatation and hence generalized vascular disease was confirmed which caused hypertension along with ischaemic nephropathy in the patient.Discussion- Our case represents a rare autoimmune disease leading to pulmonary hypertension and renal artery stenosis. Whenever young female patients present with associated pulmonary as well as renal signs and symptoms, Takayasu arteritis should be considered as a differential diagnosis,especially if there is discrepency in blood pressure levels in all four limbs.